Adsorption of perfluorinated compounds on thin-film composite polyamide membranes - Kwon, Young-Nam (2013)
The adsorption behavior of perfluorinated compounds (PFCs), of various chain lengths and two different functional groups, on widely used thin-film composite polyamide membranes has been investigated. Three commercially available polyamide membranes and two classes of PFCs were evaluated: Dow-Filmtech BW30, NF90, and NF270 membranes; perfluorosulfonic and perfluoroalkanoic acid with 5, 7, 9, and 11 carbon atoms. The adsorption of PFCs on the membranes strongly depended on the active skin-top layer material of the membranes, solution chemistry, and structure of PFCs. The piperazine based NF270 membrane showed higher adsorption of PFCs compared to BW30 and NF90 membranes (FT-30 type membranes). The BW30 membrane, which has a coating layer of aliphatic carbons and hydroxyl groups on the surface of the polyamide substrate, had less interaction with PFCs than the NF90 polyamide membrane had. The adsorption of PFCs increased with increasing ionic strength, decreasing pH, and in divalent ion solutions. PFCs with longer chain lengths and more hydrophobic functional groups showed more attractive interactions with thin-film composite membranes and, thus, greater adsorption on the membranes.